The Role of User-Interface in a Medical Expert System - Hudson, D.L. (1985)
Expert systems have been designed for numerous medical applications. Although many of these systems have performed very well in experimental testing, very few are in actual clinical use. One continuing issue in the design of these systems is the type of user interface, and consequently the ease of use of the system. EMERGE, a rule-based expert system designed for analysis of chest pain, was originally designed with two types of user interface: a questioning mode in which the user answers questions with y, n, or?, and a data-driven mode in which information in free-format phrases can be entered directly. EMERGE was tested both retrospectively and prospectively. During the prospective analysis, it was found that a third, menu-driven mode of user interface was desirable. In this mode, the user can choose selections from a menu in a manner similar to many microcomputer applications. In this paper, the use and design of these user interfaces is discussed.